Application of Cigeratte Filter from Algae Spyrogira peipingensis to Reduce Nicotine, Tar, and Carbon Monoxide - Bahri, Syamsul (Hasanuddin University, 2017)
Algae Spirogyra peipingensis is a group of green algae from the order Zygnematales. Spirogyra algae serves as a bioremediation agent. In addition Spirogyra algae has great potential in reducing toxin levels in cigarette smoke. Because the biomass of alga Spirogyra has an irregular shaped surface texture and consists of amino acid, amide, carboxylic, hydroxyl, and carbonyl group that can bind various heavy metals and other harmful compounds. Alga Spirogyra peipingensis samples used are algae from Bone, South Sulawesi. Prior to the trial, the first pretreatment and processed to become powder. Algae powder was then applied to cigarette filters and tested on several respondents. Results showed that there was a significant decreaseÂ tar, nicotine and carbon monoxide levels in cigarette smoke by using Spirogyra peipingensis algae but the most significant decrease of carbon monoxide, while tar and nicotine decreased even though not as high as carbon monoxide.Â